(untitled) (The Lumbini Journal of Business and Economics, 2025)
Purpose: The study aims to investigate the role of energy consumption, especially petroleum and electricity consumption, alongside gross capital formation on the economic growth of Nepal. Methods: The study applies econometric analysis using time series data from 1980/81 to 2023/24. The analysis starts with the Augmented Dickey-Fuller test to check for the stationary data, the Johansen cointegration test for long-run relationships, and Granger causality test to ascertain the direction of causality among the variables. Results: The finding reveals that there is a long-run relationship between the variables. Vector Error Correction Model result reveals that GCF serves as a primary adjusting variable in long run after short run shocks. Petroleum consumption and gross capital formation have positive significant on GDP in short run but electricity consumption shows less impact on short run. Granger causality result suggests that there is unidirectional causality from GDP to GCF, GCF to EC, and PC to GCF. Also, a bi-directional causality in PC and EC, but no direct causality from energy consumption to economic growth. Conclusion: Energy consumption is an influencing factor in the economic growth of Nepal. The result suggests diversifying energy sources, reducing dependence on petroleum, and strengthening investment in energy sector to increase the economic growth of the country to achieve sustainable and balanced growth.